تدريس المفردات في كتاب العربية بين يديك (دراسة وصفية تحليلية): Teaching Vocabulary in the Book "Al-Arabiyah Baina Yadaik" (Descriptive-Analytical Study) - Ronny Mahmuddin (البصيرة: مجلة الدراسات الإسلامية, 2026)
This research aims to describe and analyze the methods of teaching vocabulary in the book Arabic at Your Hands, through a descriptive and analytical study based on the qualitative approach using the library method. The content of the book was analyzed to reveal methods of presenting vocabulary and patterns of exercises associated with it. The results of the research concluded that the book relies on a variety of methods for teaching vocabulary, through the use of pictures, automatic exercises based on simulation and repetition, in addition to meaning exercises that contribute to enhancing understanding of vocabulary.The book also distinguishes between two types of vocabulary: basic vocabulary related to dialogue, and additional vocabulary that aims to expand the learner's linguistic vocabulary. The results indicate that the book focuses largely on mechanical and semantic exercises, with a relative weakness in employing communicative exercises, which requires developing this aspect to achieve integration in vocabulary teaching.